THE IMPLEMENTATION OF CHARACTER-BASED HOLISTIC EDUCATION MODEL TO INSTALL ISLAMIC RELIGIOUS VALUES FROM EARLY - Dede Rini; Irma Yuliantina (Jurnal Ilmiah POTENSIA, 2024)
The purpose of this study is to determine the planning, implementation and evaluation of the implementation of a character-based holistic education model to instill Islamic religious values ​​from an early age in Kartina Kindergarten, Garut Regency. The research approach used is qualitative with field study methods used to answer research objectives. Data collection techniques by way of observation and interviews. The results of the study show that planning the education curriculum at Kartina Kindergarten, Garut Regency aims to carry out Islamic Religious Education from an Early Age so that children comply with religious teachings, and create good social interaction between themselves and God, humans and the environment. Implementation of this education in Kartina Kindergarten, Garut Regency with an integrated learning process between the fulfillment of knowledge and morals. The evaluation is carried out regularly both per theme and per month to ensure the program is running.